To what Extent Open Government Data (OGD) Portals Accessibility under the Indonesian Provincial Government? - Al Fauzi Rahmat; Amnat Arthan; Muhammad Ade Putra (Universitas Muhammadiyah Tangerang, 2023)
This article aims to examine the accessibility of providing open data services under open government data (OGD) portals at the local government level, where our have found 17 OGD official websites and have been selected under the control of several provincial governments in Indonesia. For this paper, we employed the highlighted WAVE and AChecker tools. Significantly, findings indicate that the most of 17 OGD portals have failed accessibility assessments with striking viewpoints obtained in the â€œARIAâ€ tool and followed by the â€œStructural Elementsâ€ sections analyzed using the WAVE tool, wherein only OP11 has a range of passed website accessibility tests. It is also consistent with the findings by the AChecker tool in the â€œKnown Problemâ€ and also â€œLikely Problemâ€ sections pointed out that passed the test. However, it should be noted that the only three OGD websites that passed the test by AChecker were OP3, OP9, and OP16. As a result, there is a constant high frequency of â€œpotential problemsâ€ discovered by AChecker than by the WAVE tool on the OGD websites.Â Artikel ini bertujuan untuk mengkaji aksesibilitas penyediaan layanan data terbuka di bawah portal data pemerintah terbuka (OGD) di tingkat pemerintah daerah, di mana kami telah menemukan 17 situs web resmi OGD dan telah dipilih di bawah kendali beberapa pemerintah provinsi di Indonesia. Untuk makalah ini, kamiÂ telahÂ menggunakanÂ alatÂ WAVE dan AcheckerÂ sebagai sorotan pengujian. Secara signifikan, temuan menunjukkan bahwa sebagian besar dari 17 portal OGD telah gagal dalam penilaian aksesibilitas dengan sudut pandang mencolok yang diperoleh dalam alatÂ â€œARIAâ€ diikuti oleh bagian â€œElemen Strukturalâ€ yang dianalisis menggunakan alat WAVE, di mana hanya OP11 yang memiliki rentang aksesibilitas situs web yang lulus tes. Ini juga konsisten dengan temuan alat AChecker di bagianÂ â€œMasalah yang Diketahuiâ€Â dan jugaÂ â€œKemungkinan Masalahâ€Â yang ditunjukkanÂ telahÂ lulus uji. Namun, perlu dicatat bahwa hanya tiga situs web OGD yang lolos uji oleh AChecker adalah OP3, OP9, dan OP16. Akibatnya, ada frekuensi tinggiÂ â€œmasalah potensialâ€Â yang ditemukan oleh AChecker daripada oleh alat WAVE di situs web OGD.